Trip to Nicaragua with the Tufts group BUILD in coordination with the organization Bridges to Community. Photo 036 - Ko, Melody (Tufts Archival Research Center, 2008)
Trip to Nicaragua with the Tufts group BUILD in coordination with the organization Bridges to Community.